Fully Principally Extending Module - Shallal, Emad (Iraqi Journal of Science, 2024)
In this work, We introduce the concepts of an FP-Extending, FP-Continuous and FP-Quasi-Continuous which are stronger than P-Extending, P-Continuous and P-Quasi-Continuous. characterizations and properties of FP-Extending, FP-Continuous and FP-Quasi-Continuous are obtained . A module M is called FP-Extending ( FP-Continuous, FP-Quasi-Continuous) if every submodule is P-Extending (P-Continuous, P-Quasi-Continuous) .